The Neural Mechanism Underlying The Effect of Musical Training on Phonological Awareness of preschoolers : A Meta-Analysis - Афаф Мамдух Мохамед Баракат; Басант Абдельмонем Альхам Альхам Махмуд; Ранда Мохамед Мабрук Ельмаграбі (Психолінгвістика)
Introduction. This paper reviews the research evidence on the impact of music training on children's phonological awareness in the past decade, and discusses the theoretical basis and explanatory model of how music training may promote phonological awareness.